In vivo computer-aided diagnosis of colorectal polyps using white light endoscopy - García-Rodríguez, Ana; Tudela, Yael; Córdova, Henry; Carballal, Sabela; Ordás, Ingrid; Moreira, Leticia; Vaquero, Eva; Ortiz, Oswaldo; Rivero, Liseth; Sánchez, F. Javier; Cuatrecasas, Miriam; Pellisé, Maria; Bernal, Jorge; Fernández-Esparrach, Glòria (Endoscopy International Open, 2022)
Background and study aims Artificial intelligence is currently able to accurately predict the histology of colorectal polyps. However, systems developed to date use complex optical technologies and have not been tested in vivo. The objective of this study was to evaluate the efficacy of a new deep learning-based optical diagnosis system, ATENEA, in a real clinical setting using only high-definition white light endoscopy (WLE) and to compare its performance with endoscopists.Methods ATENEA was prospectively tested in real life on consecutive polyps detected in colorectal cancer screening colonoscopies at Hospital Clínic. No images were discarded, and only WLE was used. The in vivo ATENEA’s prediction (adenoma vs non-adenoma) was compared with the prediction of four staff endoscopists without specific training in optical diagnosis for the study purposes. Endoscopists were blind to the ATENEA output. Histology was the gold standard.Results Ninety polyps (median size: 5 mm, range: 2–25) from 31 patients were included of which 69 (76.7 %) were adenomas. ATENEA correctly predicted the histology in 63 of 69 (91.3 %, 95 % CI: 82 %–97 %) adenomas and 12 of 21 (57.1 %, 95 % CI: 34 %–78 %) non-adenomas while endoscopists made correct predictions in 52 of 69 (75.4 %, 95 % CI: 60 %–85 %) and 20 of 21 (95.2 %, 95 % CI: 76 %–100 %), respectively. The global accuracy was 83.3 % (95 % CI: 74%–90 %) and 80 % (95 % CI: 70 %–88 %) for ATENEA and endoscopists, respectively.Conclusion ATENEA can accurately be used for in vivo characterization of colorectal polyps, enabling the endoscopist to make direct decisions. ATENEA showed a global accuracy similar to that of endoscopists despite an unsatisfactory performance for non-adenomatous lesions.